From Hasan Ziyayi Mostari’s Divan: Verses in Persian (Ziyāyī Hasan Ċalabī b. ‘Alī al-Mostārī) (Prilozi za orijentalnu filologiju, 2017)
Hasan b. Ali al-Harsaki, whose literary nickname is Ziyayi Čalabi or Ziyayi al-Mostari, is one of the oldest Bosnian divan poets (16th century). He was very educated, presented with calligraphy and inspired poet, who wrote the extensive Divan with poetry in Turkish and Persian languages (625 poems). So far, the only known copy of Divan there has been in the Selimiyya Library in Edirna (T. 811-2127).A qasida (27 verses), a qit’a and 14 gazels are included in his Divan in Persian language as well.After analysing of his poetry we can conlude that Ziyayi had a broad education and was well-acquainted with poetry of Persian classics, their style and metrics, values and characteristics of the poetry of each separated poet as well.The all Ziyayi’s verses in Persian language have been brought spirited, daring, with polished language and lightsomely, although they sometimes have a powerful presence of disenchantment of some kind lying behind and radiate resignation and show calming down, which points to his abiding longing for unrealized goals.This paper brings Ziyayi’s poetry in Persian from his Divan, which to date have not been translated into Bosnian.